A country of cities : a manifesto for an urban America - Chakrabarti, Vishaan (New York : Metropolis Books, 2013)
Argues that well-designed cities are the key to solving the United States great national challenges: environmental degradation, unsustainable consumption, economic stagnation, rising public health costs and decreased social mobility.
Includes bibliographical references and index.
ARC
Keywords: City planning -- United States; Cities and towns -- Growth -- Social aspects -- United States; Sustainable development -- United States; Architecture